Symptomatic burden amongst myeloproliferative neoplasm patients: mpn-10 prospective assessment in a portuguese cohort - Maria Sarmento; Sandra Ponte; Maria José Monteiro; Zilda Moura (Associação de Enfermagem Oncológica Portuguesa, 2021)
Introduction: Myeloproliferative neoplasms (MPN), including polycythemia vera (PV), essential thrombocythemia (ET), and myelofibrosis (MF), significantly impact patients' quality of life (QoL). The symptom burden assessment and continuous monitoring using the MPN Symptom Assessment Form Total Symptom Score (MPN-10) allows detecting symptomatic changes that may be signs of disease progression and can be used as an indicator of the need to reassess disease progression and/or therapeutic approach.   Methods: Prospective multicenter registry of Portuguese MPN patients, including patients' demographics and clinical characterization, and disease symptomatic burden based on MPN-10.   Results: Overall, 324 patients were included, male to female ratio 0.7:1, median age 71 years old, median disease duration >3 years. Most patients had ET (63%), 24% PV, and 13% MF. Around 70% were being treated with hydroxyurea, 31% were on recommended low-dose aspirin, 9% needed phlebotomy, 4% received ruxolitinib, and <2% interferon. Most reported symptoms include fatigue, inactivity, itching, and concentration problems. PV and ET patients' total symptom score significantly improved from baseline until last follow-up visit. The itching had a significant improvement over baseline for PV patients, as did fatigue, inactivity, concentration problems, and night sweats in ET patients.   Conclusions: The systematic application of the MPN-10 led to a more in-depth knowledge of patients and their symptoms, which, together with analytical changes, motivated therapeutic readjustments that led to QoL gains. Future analysis of this cohort should be conducted to refine these results.